HALOSTABLE ALKALINE AMYLASE AND PROTEASE FROM AN EXTREMELY HALOALKALIPHILIC ARCHAEON, NATRINEMA SP. SSBJUP-1 ISOLATED FROM LONAR LAKE. - J. U. PATIL; S. S. BAJEKAL (International Journal of Pharma and Bio Sciences, 2015)
An extremely haloalkaliphilic archaeon Natrinema sp. SSBJUP-1 showing potent amylolytic and proteolytic activities was isolated from the saline alkaline Lonar Lake, India. Amylase and protease were active over the neutral to alkaline pH range from 6 to 9. Amylase was more stable over a narrower temperature range of 40-60oC than the protease but had the higher optimum (55oC) for activity. By contrast, protease was active over a broader range 10-75oC with an optimum of 40oC. The amylase was stable over a broader salinity range, but with an optimum salt concentration of 10-12%, whereas the protease was with a higher optimum concentration of 18% salt in the reaction mixture. Calcium and Magnesium behaved as activators for both enzymes while Copper was an activator for protease while being an inactivator for amylase. Amylase was highly tolerant to five commercial detergents tested while the protease was tolerant only to one.